Teaching a five-paragraph essay - Bastola, Ganesh Kumar (Journal of NELTA, 2018)
Writing an essay requires usto think through whatwe are going to do. Every essay has a beginning, middle, and an end (Levin, 1997). In a five-paragraph essay, the first paragraph is generally understood as introduction. An effective introduction demands readers’ interest and give them a sense of the topic and purpose (Gardner, 2005). The next three paragraphs consist of the body of the essay. The body of the essay explains and supports the thesis with details; further develops ideas in a clear sequence. The fifth paragraph is conclusion. It incorporates the importance of the thesis statement, reflects on the larger significance of the topic, and brings the essay to a logical manner (Gardner, 2005).